THE SYIAH TURMOIL IN A SHARIA SOIL: An Anthropological Study of Hidden Syiah Minority Entity in Contemporary Aceh - Chaidar, Al (Department of Anthropology, 2018)
Syiah had ever been a major Islamic denomination in Aceh for centuries. This research is not only about how much classical Sharia rules can be a reference to resolve political problems of majority and minority division, but also to examine the power of sharia in protecting and marginalising Syiah. Based mainly on classical Snouck Hurgronje ethnography, this study elaborate the the former sharia as a living law in old Aceh and comparing it with recent legal pluralism of Aceh nowadays. With a spectacular growing of traditional Dayah (conservative Sunnism) in present politics, and the transnational Salafi Wahabism intrusion into Aceh, the position of Syiah is at the most tip of the edge in society. Those who embraced or converted Syiah are living scatteredly all over Aceh by a unique ideo-syncretic way of survival. Achenese Syiah are now facing hardest situation in this Syafiidominated land and hardened with the rage of Wahabism